Implementasi QRIS pada UMKM Lokal di Pusat Pemerintahan Wilayah Perbatasan Negara - M. Irfani Hendri; Clara Jessica Melcie; Lucky Saputra; Muhammad Naufal Shofwan; Renditha Nerazzury; Hajijah hajijah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting economic growth, particularly in border regions where digital literacy among business actors remains low. In Dalam Kaum Village, Sambas Regency, most MSMEs have not yet utilized digital payment systems such as QRIS due to limited understanding and lack of technical assistance. In fact, QRIS can improve transaction efficiency as it is easy to use, secure, and integrated with various digital wallets. This community service program was implemented in three stages: (1) identifying MSMEs that had not yet adopted QRIS, (2) providing assistance in creating DANA Business accounts to obtain QRIS, and (3) conducting post-implementation evaluations. A total of 15 MSMEs successfully obtained QRIS, with 80% of respondents stating that the system facilitated transactions and enhanced business professionalism. Reported benefits included faster transactions, more organized bookkeeping, and the elimination of the need for cash change. The results indicate that with proper guidance, MSMEs can adapt to digital payment technologies. Therefore, QRIS implementation should be continuously developed through collaboration among government, service providers, and academic institutions to strengthen MSME competitiveness in border areas.